La pluralité des cultures : une menace pour l’ego - Nkejabahizi, Jean Chrysostome (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
We live in diverse places with variable experiences due to ecological, geographical, historical environment. That creates difference in terms of knowledge and skills, lifestyles, values, which constitutes cultural diversity. The contact between ego and others creates a feeling of insecurity because any foreign thing seems to be strange and threatening. This explains why we have always a negative view about others. We need a period of appreciation and recognition, for being closed with and learn a share living. This exercise which took place from Greeks and Romans Antiquity has not succeeded in exorcizing the fear and avoidance of others, despite the invention of some notions like tolerance and culture dialogue. That is still being a challenge for humanity as it is narrated by some travel accounts.